2019
DOI: 10.18632/aging.102569
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA methylation markers in the diagnosis and prognosis of esophageal cancer

Abstract: The early diagnosis and accurate prognosis prediction of esophageal cancer is an essential part of improving survival. However, these diseases lack effective and specific markers. A total of 1,744 samples of HumanMethylation450 data were integrated to identify and validate specific methylation markers for esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC) as well as for Barrett’s esophagus (BE) using The Cancer Genome Atlas and the Gene Expression Omnibus. The diagnostic and prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…Indeed, in treatmentnaïve tumors, the three selected genes disclosed different methylation levels among ESCC and EA, variably comparing to normal esophageal tissue samples. Differential methylation patterns between ESCC and EA have been previously reported and are in line with our results (31,32). In particular, available data support the value of identi cation speci c ESCC methylation panels to enable early detection (16,33,34).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in treatmentnaïve tumors, the three selected genes disclosed different methylation levels among ESCC and EA, variably comparing to normal esophageal tissue samples. Differential methylation patterns between ESCC and EA have been previously reported and are in line with our results (31,32). In particular, available data support the value of identi cation speci c ESCC methylation panels to enable early detection (16,33,34).…”
Section: Discussionsupporting
confidence: 92%
“…ESCC and EA displayed different cancer-speci c methylation patterns. Accordingly, differential methylation patterns have been previously reported between ESCC and EA (38,39). Indeed, in treatmentnaïve tumors, the three selected genes disclosed different methylation levels among ESCC and EA, variably comparing to normal esophageal tissue samples.…”
Section: Discussionmentioning
confidence: 83%
“…Plasma samples of patients suspected of having ESCC might be collected and analyzed for these hypermethylation events. 26,27 DNA methylation can alter the ability of transcription factors to bind DNA and regulate gene expression. 21,28,29 Dong et al 21 revealed that the hypermethylation within the proximal promoter of ZNF667-AS1 or ZNF667 influenced the binding ability of transcription factor E2F1 binding and the following transcriptional activation and expression of them.…”
Section: Discussionmentioning
confidence: 99%